POLAR CONSTRUCTION EQUIPMENT - LGP D4 SERIES D SNOW TRACTOR. - Taylor, Douglas (1966)
A Caterpillar D4 Series D (D4D) tractor was purchased and modified during FY 65 to produce a low ground pressure (LGP) snow tractor with less weight and size than previous LGP D4C's, but with the same general antarctic construction capability. The basic D4D with accessories was about 700 pounds heavier than the basic D4C, but the modified D4D was 1,440 pounds lighter than the similarly modified D4C. This reduction in weight was made possible by an increase in the allowable ground bearing pressure and by the use of aluminum track shoes in place of steel. The LGP D4D gave generally satisfactory service during 210 hours of operation in various antarctic tasks during the winter of 1965-66 (antarctic summer). The aluminum tracks showed no noticeable wear.